Resource sharing in cataloging work among school libraries : some possible actions and strategies / Fuziah Mohd. Nadzar - Mohd. Nadzar, Fuziah (Faculty of Information Management, 2005)
Covers the aspect of resource sharing in school libraries or school resource centres, pertaining to the technical services activities of descriptive cataloging, classification and assignment of subject headings. Provides an overview of the current state of these tasks and describes some possible actions and strategies that can be implemented to ensure the success of the concept of resource sharing in cataloging and classification work. Only then will the changing role of the teacher librarians of the 21st century to that of an "information manager" effectively take shape.